Metabolomic screening and urolithins metabotypes identification in the urinary metabolome of Costa Rican volunteers after blackberry (Rubus adenotrichos)-based drink consumption - Fallas Ramírez, José Manuel (2024)
Background: Besides providing nutritional value, functional foods have potential beneficial effects on health. Consumers worldwide seek food products with added value based on physical and mental well-being. Objective: This study aimed to analyze the urinary metabolome of volunteers who consumed a drink based on Costa Rican blackberries (Rubus adenotrichos) to identify the presence of urolithins and other possible bioactive compounds related to beneficial effects on health. Methods: Fifteen healthy non-smoking male volunteers aged between 19 and 43 years old who consumed 250 ml of blackberry-based drink for breakfast for eight consecutive days were selected. Urine samples were obtained before and after drink consumption, which were submitted to analysis by Ultra-Performance Liquid Chromatography coupled to a Mass Detector (UPLC/ESI-Q-TOF-MS). Subsequently, a metabolomic analysis of the results was performed to identify the presence or absence of urolithins and other bioactive metabolites related to blackberry juice consumption. Results: It was possible to detect high intensity presence of urolithin A (n = 6) and high intensity presence of both urolithin A and B (n = 5) in urine samples in several volunteers. However, finding them was impossible in others, or they were at very low intensities (n = 4). Likewise, it was possible to identify Menth-1-en-4,8 diol glucuronide and 1-O-E-Cinnamoyl-(6-arabinosylglucose) as other compounds related to the consumption of blackberries. Conclusions:The consumption of Costa Rican blackberries allowed us to demonstrate the presence of three metabotypes within the study population: 40% of strong urolithin A (UAP) producers, 33.3% of both urolithin (A and B) producers (UBP), and 26.7% of weak urolithinAproducers (0P). Finally, it is recommended to carry out more research in this regard, considering a greater number of volunteers and including people of both sexes.